Salvaging The Marginalized: Supporting Service Teachers’ Skills in Extensive Reading Pedagogies for Nomadic Pastoralist Children in Kenya - Mudogo, Benard; Gervasio, Miriti; Ouko, Susan (International Journal of Language Teaching and Education, 2025)
The societal impacts of enhancing teacher capacity in the underserved Arid and Semi-Arid Lands (ASAL) are significant in improving education policy and practice; yet, few studies have investigated the continuous professional support that teachers need to provide quality and inclusive education in such contexts. This research reports on the implementation of a teacher capacity-building action research project aimed at supporting primary school children's Extensive Reading (ER) activities in the context of underserved and least developed areas of the ASAL in Lodwar, Turkana County, Kenya. The trainees in the ER programme were 30 teachers from ten primary schools. Study results indicate that teachers were able to help learners develop self-directed ER, which was a positive step towards initiating a reading culture in English as a Second Language (ESL). Moreover, the reading comprehension results showed that ER had somewhat gradual significance in increasing ESL learning outcomes. However, students’ motivation to read requires the sustained development of new reading strategies, accompanied by a continuous monitoring plan, to achieve considerable improvement.